Penggunaan Lexical Bundles pada Tulisan Ilmiah Mahasiswa Sarjana dan Pascasarjana Jurusan Pendidikan Bahasa Inggris - Try Retno Sugiarti; Nevita Indah Fitrianasari; Terry Sulistyorini (English Education Department, 2018)
Studies related to the ubiquity of lexical bundles used by undergraduate and graduate students in writing their academic writing, more specifically skripsi and thesis, seems to be limited. As an important defining feature of academic discourse and a significant component of fluent linguistic production, its existence in writing not only can contribute coherence in a text but also can determine the writing ability of a writer, either professional or novice one (Hyland, 2012, p. 166; Cortes, 2004, p. 397). Therefore, it is necessary to conduct this study in order to know the most frequent forms, structures, and functions of lexical bundles used by undergraduate and graduate students in composing their skripsi and thesis. It was revealed that (1) graduate students use more varied bundles rather than undergraduate students; (2) both students tend to use the same structure of noun phrase with of fragment bundles; (3) undergraduate students tend to use research-oriented bundles, while graduate students prefer to use more text-oriented bundle.